Le changement en association s'adapter, innover, résister - BUCOLO, Elisabetta; Haeringer, Joseph (RESSOR, 2022)
Whether forced or deliberate, change is an integral part of any organisation. It necessarily concerns all those involved in associations: managers, professionals or volunteers, but also users of a service. If change is not to be imposed, it must be explained, analysed and supported. It is therefore essential to explore collective representations, understand the rationale for action and identify the meaning given to it by the players involved.